Jerzy Osiatynski (1941-2022) - Jan Toporowski; Jerzy Osiatyński (PSL Quarterly Review, 2022)
This obituary describes Jerzy Osiatynski's life and works, recalling his origins and early life, the academic and activity, and the personal and intellectual links with Micha± Kalecki.
Keywords: B32; B24; E11; 330; Jerzy Osiatynski; obituary; Micha± Kalecki